Do anti-platelet drugs improve duration of continuous renal replacement therapy? A retrospective cohort study in cardiac ICU patients. Issue 10 (October 2021) - Gupta, Vivek; Aslam, Naved; Chhabra, Shibba Takkar; Makkar, Vikas; Mohan, Bishav; Kapoor, Samir; Singh, Vikram Pal; Kumar, Rajiv; Grover, Suvir; Kaur, Gurkirat; Sethi, Suman; Kaur, Simran; et al.
Objective: The objective of this study was to investigate the impact of anti-platelet drug/s on duration of continuous renal replacement therapy (CRRT) in those patients where anti-coagulants were not used due to certain contraindications and in cases where patients were on anti-platelet drugs and were given anti-coagulant during CRRT. Method: This single-center, retrospective cohort study was conducted using the medical records patients treated with CRRT in the cardiac ICU of the inpatient urban facility, located in North India. Data was collected from only those patients who received CRRT for the duration of at least 12 h. Patient's in NAC group were not on any anti-platelet/s and did not receive anti-coagulant during CRRT. AC and AP group patients received anti-coagulant alone or were already on anti-platelet/s and did not receive anti-coagulant respectively while ACAP group patients were on anti-platelet drug/s and also received anti-coagulant during CRRT. Result: Patients in AC, AP, or ACAP group showed significantly ( p  < 0.001) higher CRRT filter life compared to NAC group. The median CRRT filter life was significantly higher in the ACAP group compared to AC ( p  < 0.05) and AP ( p  < 0.001) groups. Conclusion: This study indicates that systemic anti-platelet therapy can provide additional support in critical patients undergoing CRRT even with or without anti-coagulant therapy. However, the increase in CRRT filter life was more profound in patients who were on anti-platelet/s and also received anti-coagulant drug/s during CRRT.